2011
DOI: 10.1021/ja2021476
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Thermal Cyclotrimerizations of Fluoro- and Chloroacetylenes: Density Functional Theory Investigation and Intermediate Trapping Experiments

Abstract: Theoretical studies of the mechanisms of the thermal cyclotrimerization of fluoro- and chloroacetylenes, which were reported by Viehe and Ballester, respectively, were conducted with the aid of density functional theory calculations of the (U)B3LYP functional, indicating that the thermal cyclotrimerizations of fluoro- and chloroacetylenes involve tandem processes of regioselectively stepwise [2+2] and stepwise [4+2] cycloadditions. These tandem processes generate 1,2,6-trihalo-Dewar benzenes and 1,2,4-trihalo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 82 publications
4
45
0
1
Order By: Relevance
“…In Figure 1 , we can see the alkyne cyclotrimerization reported by Yao et al. [ 34 ].
Figure 1 Mechanism of the cyclotrimerization of fluoroacetylene reported by Yao et al.
…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…In Figure 1 , we can see the alkyne cyclotrimerization reported by Yao et al. [ 34 ].
Figure 1 Mechanism of the cyclotrimerization of fluoroacetylene reported by Yao et al.
…”
Section: Introductionmentioning
confidence: 65%
“…(b) Thermodynamic parameters: ΔG, ΔH, ΔE 0 (kcal/mol) profiles along the IRC, reported by Yao et al. using DFT calculations [ 34 ]. Note: Yao et al [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Calculations for 80b (Y = F) and 80c (Y = Cl) were also performed by UB3LYP/6–31G*. These results show that the 1,1′ dimerization is energetically favored by more than 5 kcal mol –1 over to the corresponding 2,2′ dimerizations . The results summarized in Figure suggested that 80b (Y = F) and 80d (Y = OMe) should be good candidates for trapping experiments.…”
Section: Resultsmentioning
confidence: 97%
“…Those that have been reported are often highly reactive and, in marked contrast to fluoroalkanes, fluoroalkenes and fluoroaromatic compounds, fluoroalkynes readily undergo oligomerization reactions. For example, FC≡CF is unstable at temperatures above −196 °C and t BuC≡CF undergoes cyclotrimerization below 0 °C . Fluoroalkynes having perfluoroalkyl groups, however, appear to have greater stability .…”
Section: Methodsmentioning
confidence: 99%